Open-cage benzocyclobutenyl polysilsesquioxane thermosetting resin as well as preparation method and application of open-cage benzocyclobutenyl polysilsesquioxane thermosetting resin

Through the molecular-level homogenization technology of open-cage benzocyclobutenyl polysilsesquioxane, the problem of difficult to take into account both dielectric performance and thermal stability in the electronic communication field is achieved, and low dielectric constant and low Dielectric loss, high heat resistance and flexibility thermosetting resin material, suitable for high frequency signal transmission and high temperature environments.

CN119285954AActive Publication Date: 2025-01-10NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202411617076.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-10
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The prior art is difficult to develop insulating materials with low dielectric constant, low dielectric loss, good thermal stability and appropriate flexibility, which cannot meet the demand for high-frequency signal transmission in the electronic communication field, especially at high temperatures, materials are introduced. Electrical performance and flexibility are difficult to take into account.

Method used

Open-cage benzocyclobutenyl polysilsesquioxane (POSS) is used to form an organic-inorganic thermosetting resin with a moderate crosslinking network through molecular-level homogenization, and the special structure is used to achieve low dielectric properties and High heat resistance and flexible properties.

Benefits of technology

It realizes thermosetting materials with ultra-low dielectric constant and dielectric loss at 1MHz frequency, with high heat resistance and flexibility, suitable for 5G electronic packaging, printed circuit boards and radar radomes, and overcomes traditional materials in high Inadequate performance problem at frequency and high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285954A_ABST
    Figure CN119285954A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of organic-inorganic thermosetting resin materials, and particularly relates to open-cage benzocyclobutenyl polysilsesquioxane thermosetting resin as well as a preparation method and application thereof. The invention provides open-cage benzocyclobutenyl polysilsesquioxane. The structural formula of the open-cage benzocyclobutenyl polysilsesquioxane is shown as a formula 1 or a formula 2. The thermosetting resin based on the open-cage benzocyclobutenyl polysilsesquioxane disclosed by the invention has an ultralow dielectric constant and low dielectric loss; the thermosetting resin prepared by the preparation method has high heat resistance and good flexibility, can be prepared into a firm block material by a casting method, and can be prepared into a flexible thermosetting resin film by a spin coating or dispensing method. The homogeneous intramolecular organic-inorganic hybrid thermosetting resin is prepared by taking the open-cage POSS as a monomer through thermal crosslinking of the open-cage POSS, and the problems that the POSS is non-uniformly dispersed, the threshold value of the addition amount is low and the improvement of the material performance is limited when a polymer is modified by the POSS are solved. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic-inorganic thermosetting resin materials, and specifically relates to an open-cage benzocyclobutene-based polysilsesquioxane thermosetting resin and a preparation method and application thereof. Background Art

[0002] The rapid development of the Internet of Things (IOT) and high-frequency (5G) communication technology has put forward higher requirements for the high integration of electronic devices and efficient signal transmission. This means that more functional circuits are compressed into a smaller space, which leads to increased device capacitance and resistance, and causes problems such as crosstalk noise, signal delay and power consumption. The transmission loss of electrical signals in digital circuits mainly includes conductor loss (T LC ) and dielectric loss (T LD ) in two aspects, among which the dielectric loss (T LD ) is closely related to the dielectric constant (k) and dielectric loss (tanδ) of the dielectric material and follows the following formula:

[0003]

[0004] Among them, K is a constant, f is the frequency, and c is the speed of light. Therefore, it is urgent to develop insulating materials with low dielectric constant and low dielectric loss to meet the rapid development of electronic communication technology. In addition, it is also hoped that the developed dielectric materials have excellent thermal stability to meet the post-processing process at a high temperature of 350°C, as well as appropriate flexibility to meet the preparation and development of flexible electronic components. In summary, the development of insulating materials with low dielectric constant, low dielectric loss, good thermal stability and appropriate flexibility is of great significance to promote the development of the electrical communication industry.

[0005] Polyhedral oligomeric silsesquioxane (POSS) is a class of soluble and fusible intramolecular organic-inorganic hybrid nanomolecules, which are composed of hollow inorganic structures constructed by Si-O and hydrocarbon organic groups (R). The inorganic hollow structure of POSS has a high free volume fraction and is an ideal building block for low dielectric constant materials; its organic components are highly designable, making it widely used as a nanofiller to modify resin matrices such as epoxy resins, bismaleimide resins, cyanate resins, etc. However, due to the intrinsic polarity difference between POSS and resin materials, POSS will inevitably exist in the resin matrix as molecular clusters when added in high amounts, forming a large number of heterogeneous interfaces and leading to interfacial polarization of the composite material, which is not conducive to further reducing the dielectric constant and loss of the resin. The related technology discloses a thermosetting material based on closed-cage benzocyclobutene-based POSS (T8) self-crosslinking, which avoids the compatibility problem in traditional modification methods and achieves a large number of hollow cage structures uniformly dispersed in the resin matrix. The prepared material has low dielectric properties (~2.2). However, the closed-cage T8 structure with excessive rigidity and ultra-high functionality (=8) makes the cured product brittle and difficult to use in practice. Summary of the invention

[0006] In view of this, the object of the present invention is to provide an open-cage benzocyclobutene-based polysilsesquioxane thermosetting resin and a preparation method and application thereof. The open-cage benzocyclobutene-based polysilsesquioxane thermosetting resin of the present invention has good flexibility, ultra-low dielectric constant, low dielectric loss, good thermal stability and high heat resistance.

[0007] The present invention provides an open-cage benzocyclobutene polysilsesquioxane, the structural formula of which is shown in Formula 1 or Formula 2:

[0008]

[0009] In the formula, R1 is selected from the following structures: phenyl, cyclohexyl, n-pentyl, trifluoro-n-pentyl or methyl; R2 is selected from the following structures:

[0010]

[0011] R3, R4, R5 and R6 are independently selected from the following structures: H, alkyl, cycloalkyl, cycloalkyloxy, alkylthio, alkylamino, alkenylamino, aryl, heteroaryl, substituted alkyl, substituted cycloalkyl, substituted cycloalkyloxy, substituted alkylthio, substituted alkylamino, substituted alkenylamino, substituted aryl or substituted heteroaryl.

[0012] Preferably, in R3, R4, R5 and R6, the alkyl group is a C1-C6 alkyl group, the cycloalkyl group is a C3-C6 cycloalkyl group, the cycloalkyloxy group is a 3-7 membered cycloalkyloxy group, the alkylthio group is a C1-C6 alkylthio group, the alkylamino group is a C1-C6 alkylamino group, the alkenylamino group is a C2-C6 alkenylamino group, and the aryl group is a C6-C 12 The aryl group includes a benzo C3-C6 cycloalkyl group, the heteroaryl group is a 5-12 membered heteroaryl group, the 5-12 membered heteroaryl group contains 1-3 N, O or S heteroatoms, and the heteroaryl group includes a benzo 5-6 membered heterocyclic group.

[0013] Preferably, the structural formula of the open-cage benzocyclobutenyl polysilsesquioxane is as shown in Formula 3 or Formula 4:

[0014]

[0015] The present invention also provides a method for preparing the open-cage benzocyclobutenyl polysilsesquioxane described in the above technical solution, comprising the following steps:

[0016] Mixing a trialkoxysilane coupling agent, an alkali metal hydroxide, water and a first organic solvent for reflux reaction to obtain an open-cage silanol alkali metal salt polysilsesquioxane;

[0017] The open-cage silanol alkali metal salt polysilsesquioxane, vinyl chlorosilane, a first catalyst and a second organic solvent are mixed to carry out an etherification reaction to obtain a vinyl open-cage polysilsesquioxane;

[0018] The vinyl open-cage polysilsesquioxane, the benzocyclobutenyl silane compound, the second catalyst and the third organic solvent are mixed to carry out a hydrosilylation reaction to obtain an open-cage benzocyclobutenyl polysilsesquioxane;

[0019] The structural formulas of the trialkoxysilane coupling agent, vinyl chlorosilane, and benzocyclobutenyl silane compound are shown in Formula 5, Formula 6, and Formula 7, respectively:

[0020]

[0021] Preferably, the alkoxy group in the trialkoxysilane coupling agent is a methoxy group or an ethoxy group.

[0022] Preferably, the molar ratio of the alkali metal hydroxide to the trialkoxysilane coupling agent is 1:1.5 to 1:3.

[0023] Preferably, the molar ratio of the alkali metal element to vinyl chlorosilane in the open-cage silanol alkali metal salt polysilsesquioxane is 1:2 to 1:4.

[0024] Preferably, the molar ratio of the vinyl group to the benzocyclobutenyl silane compound in the vinyl open cage polysilsesquioxane is 1:1 to 1:1.5.

[0025] The present invention also provides the use of the open-cage benzocyclobutenyl polysilsesquioxane described in the above technical solution or the open-cage benzocyclobutenyl polysilsesquioxane obtained by the above preparation method in the field of electrical communications.

[0026] The present invention also provides a curing material, which is obtained by cross-linking and curing the open-cage benzocyclobutenyl polysilsesquioxane described in the above technical solution or the open-cage benzocyclobutenyl polysilsesquioxane obtained by the above preparation method.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The present invention provides an open-cage benzocyclobutene polysilsesquioxane, the structural formula of which is shown in Formula 1 or Formula 2:

[0029]

[0030] In the formula, R1 is selected from the following structures: phenyl, cyclohexyl, n-pentyl, trifluoro-n-pentyl or methyl; R2 is selected from the following structures:

[0031]

[0032] R3, R4, R5 and R6 are independently selected from the following structures: H, alkyl, cycloalkyl, cycloalkyloxy, alkylthio, alkylamino, alkenylamino, aryl, heteroaryl, substituted alkyl, substituted cycloalkyl, substituted cycloalkyloxy, substituted alkylthio, substituted alkylamino, substituted alkenylamino, substituted aryl or substituted heteroaryl.

[0033] The open-cage benzocyclobutene-based polysilsesquioxane (POSS) of the present invention not only has a larger cage-type hollow structure that expands outward, and can be made into a self-crosslinking high-heat-resistant thermosetting material, breaking through the difficulties faced by current ultra-low dielectric constant materials; and thanks to the limitation of the number of derivative sites of its special structure, it can accurately carry only 3 or 4 active organic groups involved in curing, and can effectively avoid the excessive crosslinking problem of curing of high-functionality closed-cage POSS; secondly, the inorganic cage structure of the open-cage POSS is moderately opened, and its rigidity is moderately reduced compared with that of the closed-cage POSS, which is conducive to forming a thermosetting flexible film. The present invention utilizes open-cage POSS molecules functionalized with benzocyclobutene side groups to prepare molecular-level homogeneous hybrid organic-inorganic thermosetting resins through self-thermal crosslinking, thereby achieving the unity of low dielectric properties, heat resistance and flexibility of thermosetting materials. The resin of the present invention can not only be thermally cured to form a bulk material with low dielectric constant and loss, but also can be prepared into a flexible film, meeting the demand for ultra-low dielectric constant in the field of special films, and is of great significance to radio communication fields such as 5G electronic packaging, printed circuit boards, and radar antenna covers.

[0034] The data of the embodiment show that the POSS-based thermosetting resin of the present invention has ultra-low dielectric constant and low dielectric loss at 1MHz frequency; and has high heat resistance and good flexibility, and can not only be prepared into a solid bulk material by a casting method, but also can be prepared into a flexible thermosetting resin film by a spin coating or a drop coating method. The present invention uses an open cage configuration POSS as a monomer, and prepares a homogeneous intramolecular organic-inorganic hybrid thermosetting resin by its own thermal crosslinking, thereby overcoming the problems of uneven dispersion of POSS, low addition threshold, and limited improvement of material properties when POSS is modified polymer. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0036] Figure 1 NMR of OP1B3-POSS 1 H. 13 C. 29 Si spectrum data;

[0037] Figure 2 NMR of OP2B4-POSS 1 H. 13 C. 29 Si spectrum data;

[0038] Figure 3NMR of OP0B8-POSS 1 H. 13 C. 29 Si spectrum data;

[0039] Figure 4 NMR of OP0B4T4-POSS 1 H. 13 C. 29 Si spectrum data;

[0040] Figure 5 The broadband dielectric constant data of open-cage benzocyclobutene-based POSS resin and comparative resin;

[0041] Figure 6 The broadband dielectric loss data of the open-cage benzocyclobutene-based POSS resin and the comparative resin;

[0042] Figure 7 The thermogravimetric curves of the open-cage benzocyclobutene-based POSS resin and the comparative resin;

[0043] Figure 8 Young's modulus data of open-cage benzocyclobutene-based POSS resin and comparative resin;

[0044] Fig. 9 Actual photos of the preparation of bulk materials and flexible film materials for closed cage c-OP0B8, open cage c-OP1B3 and c-OP2B4. DETAILED DESCRIPTION

[0045] The present invention provides an open-cage benzocyclobutene polysilsesquioxane (POSS), the structural formula of which is shown in Formula 1 or Formula 2:

[0046]

[0047] In the formula, R1 is selected from the following structures: phenyl, cyclohexyl, n-pentyl, trifluoro-n-pentyl or methyl; R2 is selected from the following structures:

[0048]

[0049] R3, R4, R5 and R6 are independently selected from the following structures: H, alkyl, cycloalkyl, cycloalkyloxy, alkylthio, alkylamino, alkenylamino, aryl, heteroaryl, substituted alkyl, substituted cycloalkyl, substituted cycloalkyloxy, substituted alkylthio, substituted alkylamino, substituted alkenylamino, substituted aryl or substituted heteroaryl.

[0050] In the present invention, "*" indicates a linking site.

[0051] In the present invention, the R1 is an inert organic structure of POSS, and phenyl, cyclohexyl, trifluoro-n-pentyl, n-pentyl or methyl are respectively as shown below, and the R1 is preferably phenyl;

[0052]

[0053] In the present invention, R2 is an active organic group for cross-linking in POSS; in R3, R4, R5 and R6, the alkyl group is preferably a C1-C6 alkyl group, the cycloalkyl group is preferably a C3-C6 cycloalkyl group, the cycloalkyloxy group is preferably a 3-7-membered cycloalkyloxy group, the alkylthio group is preferably a C1-C6 alkylthio group, the alkylamino group is preferably a C1-C6 alkylamino group, the alkenylamino group is preferably a C2-C6 alkenylamino group, and the aryl group is preferably a C6-C 12 Aryl, the aryl preferably includes benzo C3-C6 cycloalkyl, the heteroaryl is preferably 5-12 membered heteroaryl, the 5-10 membered heteroaryl preferably contains 1-3 N, O or S heteroatoms, the heteroaryl preferably includes benzo 5-6 membered heterocyclic group; R3, R4, R5 and R6 are preferably methyl.

[0054] In the present invention, the substitution preferably includes halogenation, and the halogenation preferably includes F, Cl, Br or I substitution.

[0055] In the present invention, the structural formula of the open cage benzocyclobutenyl polysilsesquioxane (POSS) is preferably as shown in Formula 3 or Formula 4:

[0056]

[0057] The open-cage benzocyclobutene-based polysilsesquioxane (POSS) of the present invention has good flexibility in its cured product due to its inorganic open-cage structure homogeneously dispersed at the molecular level and a moderate cross-linked network formed by low functionality.

[0058] The present invention also provides a method for preparing the open-cage benzocyclobutenyl polysilsesquioxane described in the above technical solution, comprising the following steps:

[0059] Mixing a trialkoxysilane coupling agent, an alkali metal hydroxide, water and a first organic solvent for reflux reaction to obtain an open-cage silanol alkali metal salt polysilsesquioxane;

[0060] The open-cage silanol alkali metal salt polysilsesquioxane, vinyl chlorosilane, a first catalyst and a second organic solvent are mixed to carry out an etherification reaction to obtain a vinyl open-cage polysilsesquioxane;

[0061] The vinyl open cage polysilsesquioxane, the benzocyclobutenyl silane compound, the second catalyst and the third organic solvent are mixed to carry out a hydrosilylation reaction to obtain an open cage benzocyclobutenyl polysilsesquioxane (POSS);

[0062] The structural formulas of the trialkoxysilane coupling agent, vinyl chlorosilane, and benzocyclobutenyl silane compound are shown in Formula 5, Formula 6, and Formula 7, respectively:

[0063]

[0064] In the present invention, unless otherwise specified, the materials and equipment used are commercially available products in the art.

[0065] The invention mixes a trialkoxysilane coupling agent, an alkali metal hydroxide, water and a first organic solvent for reflux reaction to obtain an open-cage silanol alkali metal salt polysilsesquioxane.

[0066] In the present invention, the alkoxy group (OR) in the trialkoxysilane coupling agent (R1Si(OR)3) is preferably a methoxy group or an ethoxy group.

[0067] In the present invention, the alkali metal hydroxide (MOH) preferably includes KOH, NaOH or LiOH. The molar ratio of the alkali metal hydroxide to the trialkoxysilane coupling agent is preferably 1:1.5 to 1:3, specifically 1:2.3 or 1:1.5, and seven R1-based trisilane alkali metal salt polysilsesquioxane (OP1M3-POSS) with an OP1 open cage configuration and eight R1-based tetrasilane alkali metal salt polysilsesquioxane (OP2M4-POSS) with an OP2 open cage configuration can be obtained respectively. The reaction formula is as follows:

[0068]

[0069] In the present invention, the amount of water used is preferably 1 to 2 times the molar amount of the trialkoxysilane coupling agent, and more preferably 1.1 to 1.3 times.

[0070] In the present invention, the first organic solvent is preferably a low boiling point organic solvent, and the low boiling point organic solvent preferably includes acetone, tetrahydrofuran or isopropanol.

[0071] In the present invention, the concentration of the trialkoxysilane coupling agent in the first organic solvent is preferably 0.5 to 1.5 mol / L, more preferably 0.9 to 1.1 mol / L.

[0072] In the present invention, the reflux temperature is preferably to keep the solvent slightly boiling, the time is preferably 4 to 6 hours, more preferably 5 hours, and after the reflux, it is preferably further included: cooling the reaction solution to room temperature, reacting for another 15 to 24 hours, solid-liquid separation, washing and drying the obtained solid. The solid-liquid separation method is preferably filtration; the washing reagent is preferably tetrahydrofuran, the number of times is preferably 3; the drying is preferably vacuum drying, the temperature is preferably 60°C, and the time is preferably 24 hours.

[0073] After obtaining the open-cage silanol alkali metal salt polysilsesquioxane, the present invention mixes the open-cage silanol alkali metal salt polysilsesquioxane, vinyl chlorosilane, a first catalyst and a second organic solvent to carry out an etherification reaction to obtain a vinyl open-cage polysilsesquioxane.

[0074] In the present invention, the chemical formula of the vinyl chlorosilane is R3R4ClSiCH=CH2 or R3R4ClSiCH2CH=CH2, and the R3 and R4 are independently selected from the following structures: H, alkyl, cycloalkyl, cycloalkyloxy, alkylthio, alkylamino, alkenylamino, aryl, heteroaryl, substituted alkyl, substituted cycloalkyl, substituted cycloalkyloxy, substituted alkylthio, substituted alkylamino, substituted alkenylamino, substituted aryl or substituted heteroaryl. The alkyl is preferably C1-C6 alkyl, the cycloalkyl is preferably C3-C6 cycloalkyl, the cycloalkyloxy is preferably 3-7 membered cycloalkyloxy, the alkylthio is preferably C1-C6 alkylthio, the alkylamino is preferably C1-C6 alkylamino, the alkenylamino is preferably C2-C6 alkenylamino, and the aryl is preferably C6-C 12 Aryl, the aryl preferably includes benzo C3-C6 cycloalkyl, the heteroaryl is preferably 5-12 membered heteroaryl, the 5-12 membered heteroaryl preferably contains 1-3 N, O or S heteroatoms, the heteroaryl preferably includes benzo 5-6 membered heterocyclic group; R3 and R4 are both preferably methyl.

[0075] In the present invention, the substitution preferably includes halogenation, and the halogenation preferably includes F, Cl, Br or I substitution.

[0076] In the present invention, the molar ratio of the alkali metal element to the vinyl chlorosilane in the open-cage silanol alkali metal salt polysilsesquioxane (OP1M3-POSS / OP2M4-POSS) is preferably 1:2 to 1:4, more preferably 1:3.

[0077] In the present invention, the first catalyst preferably includes an organic base, and the organic base preferably includes triethylamine, pyridine or diethylamine, and more preferably triethylamine.

[0078] In the present invention, the molar amount of the organic base is preferably the difference between the molar amount of vinyl chlorosilane and the molar amount of vinyl in the vinyl open cage polysilsesquioxane.

[0079] In the present invention, the second organic solvent is preferably an aprotic low boiling point solvent, and the aprotic low boiling point solvent preferably includes one or more of dichloromethane, tetrahydrofuran and toluene.

[0080] In the present invention, the concentration of the open-cage silanol alkali metal salt polysilsesquioxane in the second organic solvent is preferably 0.05 to 0.15 mol / L, specifically 0.067 mol / L, 0.08 mol / L or 0.1 mol / L.

[0081] In the present invention, the etherification reaction is preferably carried out under the protection of an inert gas, and the inert gas is preferably nitrogen. The temperature of the etherification reaction is preferably 0 to 25°C, specifically 20°C, and the time is 24 to 36 hours, specifically 24 hours. The structural formula of the obtained vinyl open cage polysilsesquioxane is shown in Formula 8 or Formula 9:

[0082]

[0083] In the present invention, after the etherification reaction, the process preferably further comprises: filtering to remove insoluble solids, removing the solvent by rotary evaporation, and washing and drying the obtained solids; the washing reagent is preferably methanol, and the number of washings is preferably 3 times; the drying is preferably vacuum drying, the temperature is preferably 40°C, and the time is preferably 24 hours.

[0084] After obtaining the vinyl open cage polysilsesquioxane, the present invention mixes the vinyl open cage polysilsesquioxane, a benzocyclobutenyl silane compound, a second catalyst and a third organic solvent to carry out a hydrosilylation reaction to obtain an open cage benzocyclobutenyl polysilsesquioxane (POSS).

[0085] In the present invention, the molar ratio of the vinyl group to the benzocyclobutenyl silane compound in the vinyl open cage polysilsesquioxane is preferably 1:1 to 1:1.5, and specifically may be 1:1.2.

[0086] In the present invention, the molar concentration of the vinyl open cage polysilsesquioxane (OP1V3-POSS / OP2V4-POSS) in the third organic solvent is preferably 0.05 to 0.5 mol / L, more preferably 0.06 to 0.3 mol / L.

[0087] In the present invention, the second catalyst preferably includes one or more of chloroplatinic acid, chloroplatinic acid-isopropanol solution, methylvinylsiloxane platinum complex and Karstedt catalyst.

[0088] In the present invention, the molar ratio of the mass of the second catalyst to the benzocyclobutenylsilane compound is preferably 0.025 to 0.25 g / mol, more preferably 0.05 to 0.2 g / mol.

[0089] In the present invention, the third organic solvent is preferably an inert solvent, and the inert solvent preferably includes C1-C 10 Alkane solvents and / or C6-C 12 The aromatic hydrocarbon solvent more preferably includes one or more of dichloromethane, chloroform, dichloroethane, trichloroethane, n-hexane, cyclohexane, chlorobenzene, toluene, xylene and trimethylbenzene, and specifically may be toluene.

[0090] In the present invention, the hydrosilylation reaction is preferably carried out under the protection of an inert gas, and the inert gas is preferably nitrogen. The temperature of the hydrosilylation reaction is preferably 90 to 110° C., specifically 100° C., and the time is preferably 24 to 48 hours, more preferably 30 to 36 hours. The obtained open-cage benzocyclobutene polysilsesquioxane is as shown in Formula 10 and Formula 11:

[0091]

[0092] In the structure of the open cage benzocyclobutenyl polysilsesquioxane of Formula 10 or Formula 11, n is 2 or 3 according to the structure of the above vinyl open cage polysilsesquioxane.

[0093] The present invention also provides the use of the open-cage benzocyclobutenyl polysilsesquioxane described in the above technical solution or the open-cage benzocyclobutenyl polysilsesquioxane obtained by the above preparation method in the field of radio communications.

[0094] The present invention also provides a curing material, which is obtained by cross-linking and curing the open-cage benzocyclobutenyl polysilsesquioxane described in the above technical solution or the open-cage benzocyclobutenyl polysilsesquioxane obtained by the above preparation method.

[0095] In the present invention, the solidified material comprises a resin block or a resin film, and the method for preparing the resin block comprises the following steps:

[0096] Melting open-cage benzocyclobutene polysilsesquioxane to obtain a homogeneous viscous liquid;

[0097] The homogeneous viscous liquid is subjected to a first cross-linking and curing process to obtain a resin block.

[0098] In the present invention, the melting is preferably carried out under a protective gas atmosphere; the melting temperature is preferably 80 to 90° C., the melting time is preferably 2 to 4 hours, and the melting pressure is preferably -0.08 MPa.

[0099] In the present invention, the first cross-linking curing is preferably carried out under a protective gas atmosphere; the first cross-linking curing is preferably stage curing, and the stage curing preferably includes: first stage, second stage and third stage curing, the temperature of the first stage curing is preferably 90°C, and the time is preferably 2h; the temperature of the second stage curing is preferably 210°C, and the time is preferably 2h; the temperature of the third stage curing is preferably 230°C, and the time is preferably 2h. The heating rates from the melting temperature to the temperature of the first stage curing, from the temperature of the first stage curing to the temperature of the second stage curing, and from the temperature of the second stage curing to the temperature of the third stage curing are preferably 10°C / min. During the cross-linking curing process, POSS self-crosslinks to form a three-dimensional cross-linked thermosetting resin block material.

[0100] The method for preparing the resin film comprises the following steps:

[0101] The open-cage benzocyclobutene-based polysilsesquioxane is dissolved in an organic solvent and spin-coated or drop-coated on a metal substrate. After the organic solvent evaporates, a second cross-linking curing is performed and the metal substrate is corroded in a strong acid aqueous solution to obtain a resin film.

[0102] In the present invention, the organic solvent preferably includes one or more of toluene, xylene, trimethylbenzene, diphenyl ether, cyclohexanone, dichloromethane, chloroform, acetone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide and N-methylpyrrolidone.

[0103] In the present invention, the metal substrate is preferably a metal substrate that is easily corroded by acid, and the metal substrate that is easily corroded by acid preferably includes an aluminum plate, a copper plate, an iron plate or a zinc plate.

[0104] In the present invention, the temperature for volatilization of the organic solvent is preferably 100 to 150° C., and the time is preferably 8 to 12 hours.

[0105] In the present invention, the second cross-linking and curing is preferably carried out in the same manner as the first cross-linking and curing, which will not be described in detail herein.

[0106] In the present invention, the solubility of the strong acid aqueous solution is preferably 5-15 wt %, more preferably 10 wt %.

[0107] The thermosetting resin of the present invention is an organic-inorganic hybrid thermosetting material having ultra-low dielectric constant, ultra-low dielectric loss, high heat resistance and flexibility.

[0108] To further illustrate the present invention, the open-cage benzocyclobutene-based polysilsesquioxane thermosetting resin provided by the present invention and its preparation method and application are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.

[0109] Example 1: Benzocyclobutene silyl hydride (BCB-SiH)

[0110]

[0111] Under nitrogen protection, add 120.0mmol magnesium chips, 150mL anhydrous tetrahydrofuran, 150.0mmol dimethylsilyl chloride to a 250mL dry three-necked flask, and then slowly add 100.0mmol 4-bromobenzocyclobutene (Br-BCB) at a rate of 1 drop / second; after the addition is completed, react overnight at room temperature. After the reaction is completed, remove tetrahydrofuran by rotary evaporation and add 200mL n-hexane, filter to remove insoluble inorganic salts, concentrate the solvent and distill under reduced pressure to obtain a colorless transparent liquid compound benzocyclobutene silane (BCB-SiH) totaling 13.2g, with a yield of 81.5%.

[0112] Its structural characteristics are:

[0113] 1 H-NMR (400MHz, Chloroform-d)), δ (ppm): 7.48 (1H), 7.33 (1H), 7.15 (1H), 4.50 (1H), 3.27 (4H), 0.41 (6H).

[0114] 13 C-NMR (100MHz, Chloroform-d), δ (ppm): 147.45, 145.58, 135.57, 132.43, 127.86, 122.17, 30.04, -3.31.

[0115] 29 Si-NMR (119MHz, CDCl3), δ (ppm): -16.39.

[0116] Example 2: p-Methylphenylsilane (T-SiH)

[0117]

[0118] Under nitrogen protection, add 120.0mmol magnesium chips, 150mL anhydrous tetrahydrofuran, 150.0mmol dimethylsilyl chloride to a 250mL dry three-necked flask, and then slowly add 100.0mmol p-bromotoluene (Br-T) at a rate of 1 drop / second; after the addition is complete, react overnight at room temperature. After the reaction is completed, remove tetrahydrofuran by rotary evaporation and add 200mL n-hexane, filter to remove insoluble inorganic salts, concentrate the solvent and distill under reduced pressure to obtain a colorless transparent liquid compound p-methylphenylsilane (T-SiH) totaling 12.7g, with a yield of 78.3%.

[0119] Its structural characteristics are:

[0120] 1 H-NMR (400MHz, CDCl3), δ (ppm): 7.56 (2H), 7.31 (2H), 4.55 (1H), 2.47 (3H), 0.45 (6H)

[0121] 13 C-NMR (100MHz, CDCl3), δ (ppm): 134.15, 128.78, 29.6, 21.58, -3.64

[0122] 29 Si-NMR (119MHz, CDCl3), δ (ppm): -16.39.

[0123] Example 3: Open-cage heptaphenyl tribenzocyclobutenyl polysilsesquioxane (OP1B3-POSS)

[0124]

[0125] 230.0mmol phenyltrimethoxysilane, 250mL anhydrous tetrahydrofuran, 98.6mmol sodium hydroxide (NaOH) and 290mmol deionized water were added to a 500mL three-necked flask in sequence; the mixture was reacted under reflux for 5 hours and cooled to room temperature for 15 hours. After the reaction was completed, it was filtered and the filter cake was washed three times with tetrahydrofuran. After vacuum drying at 60°C for 24 hours, 25.3g of white solid was obtained, which was open-cage heptaphenyltrisilanol sodium salt polysilsesquioxane (OP1Na3-POSS), with a yield of 78.6%.

[0126] Under nitrogen protection, 90mmol vinyldimethylsilyl chloride, 100mL anhydrous tetrahydrofuran and 60mmol triethylamine were added to a 250mL dry three-necked flask in turn, and 10mmol open-cage heptaphenyl trisilanol sodium salt polysilsesquioxane (OP1Na3-POSS) was added in five portions, and the reaction was carried out at a constant temperature of 20°C for 24h. After the reaction, the insoluble solid was filtered out, the solvent was evaporated to obtain a white solid, which was washed three times with methanol and dried in vacuo at 40°C for 24h to obtain 5.6g open-cage heptaphenyl trivinyl polysilsesquioxane (OP1V3-POSS), with a yield of 56.1%.

[0127] Under nitrogen protection, 3 mmol of open-cage heptaphenyl trivinyl polysilsesquioxane (OP1V3-POSS), 50 mL of toluene and 10.8 mmol of benzocyclobutene silane (BCB-SiH) were added to a 100 mL dry three-necked flask in sequence, and 5 drops of Karsted catalyst were added to initiate the reaction, and the reaction was carried out at 100 ° C for 30 hours. After the reaction was completed, the reaction was concentrated under reduced pressure to remove a large amount of toluene, and purified with silica gel to obtain 4.0 g of white solid, which was open-cage heptaphenyl tribenzocyclobutene polysilsesquioxane (OP1B3-POSS).

[0128] Figure 1 NMR of OP1B3-POSS 1 H. 13 C. 29 Si spectrum data, its structure is characterized by:

[0129] 1 H-NMR (400MHz, Chloroform-d)), δ (ppm): 7.65-7.00 (44H), 3.20 (12H), 0.70-0.48 (12H), 0.29 (18H), 0.19 (18H)

[0130] 13 C-NMR (150MHz, Chloroform-d), δ (ppm): 147.17, 145.85, 138.13, 132.35, 12 7.85,122.26,135.00-127.00(40C),30.43,30.28,10.64,7.63,-0.00,-3.14

[0131] 29 Si-NMR (119MHz, Chloroform-d), δ (ppm): 11.65, -1.22, -76.13, -78.65.

[0132] Example 4: Open-cage octaphenyltetrabenzocyclobutenyl polysilsesquioxane (OP2B4-POSS)

[0133]

[0134] 160.0mmol phenyltrimethoxysilane, 160mL isopropyl alcohol (IPA), 106.7mmol sodium hydroxide (NaOH) and 185.0mmol deionized water were added to a 500mL three-necked flask in sequence; the mixture was reacted under reflux for 5 hours, and cooled to room temperature for 15 hours. After the reaction was completed, it was filtered, and the filter cake was washed three times with tetrahydrofuran, and vacuum dried at 60°C for 24 hours to obtain 24.3g of white solid, which was open-cage octaphenyltetrasilanol sodium salt polysilsesquioxane (OP2Na4-POSS), with a yield of 87.0%.

[0135] Under nitrogen protection, 120mmol vinyldimethylsilyl chloride, 150mL anhydrous tetrahydrofuran and 80mmol triethylamine were added to a 250mL dry three-necked flask in sequence, and then 10mmol open-cage octaphenyltetrasilanol sodium salt polysilsesquioxane (OP2Na4-POSS) was added in five portions, and the reaction was carried out at a constant temperature of 20°C for 24h. After the reaction was completed, the insoluble solid was filtered out, and the solvent was evaporated to obtain a white solid, which was washed three times with methanol and dried in vacuo at 40°C for 24h to obtain 7.6g open-cage octaphenyltetravinyl polysilsesquioxane (OP2V4-POSS), with a yield of 54.3%.

[0136] Under nitrogen protection, 3 mmol of open-cage octaphenyl tetravinyl polysilsesquioxane (OP2V4-POSS), 50 mL of toluene and 14.4 mmol of benzocyclobutene silane (BCB-SiH) were added to a 100 mL dry three-necked flask in sequence, and 5 drops of Karsted catalyst were added to initiate the reaction at 100 ° C for 30 hours. After the reaction was completed, the reaction was concentrated under reduced pressure to remove a large amount of toluene, and purified with silica gel to obtain 5.4 g of white solid, which was open-cage octaphenyl tetrabenzocyclobutene polysilsesquioxane (OP2B4-POSS), with a yield of 88.0%.

[0137] Figure 2 NMR of OP2B4-POSS 1 H. 13 C. 29 Si spectrum data, its structure is characterized by:

[0138] 1 H-NMR (400MHz, Chloroform-d), δ (ppm): 7.55-6.95 (52H), 3.20 (4H), 0.37 (t, 8H), 0.14 (8H), 0.04 (s, 24H), 0.00 (s, 24H).

[0139] 13C-NMR (150MHz, Chloroform-d), δ (ppm): 147.17, 145.85, 138.13, 132.35, 12 7.85,122.26,135.00-127.00(40C),30.43,30.28,10.64,7.63,-0.00,-3.14

[0140] 29 Si-NMR (119MHz, Chloroform-d), δ (ppm): 11.65, -1.22, -76.13, -78.65.

[0141] Comparative Example 1: Closed-cage octabenzocyclobutene polysilsesquioxane (OP0B8-POSS)

[0142]

[0143] 200 mL of ethyl acetate (EA) and 30 mL of vinyl trimethoxysilane (VTMS) were added to a 250 mL dry three-necked flask, and stirred at 20 ° C for 30 min. Then, 42 mL of concentrated hydrochloric acid (HCl) and 18 mL of deionized water were added to a 100 mL constant pressure funnel, and added dropwise to the single-necked flask with continuous stirring. The addition was completed within 30 min, and the reaction was kept at a constant temperature of 40 ° C for 96 h. The solvent was then filtered to obtain a white powder of 14.08 g of octavinyl OP0V8-POSS with a closed cage configuration, with a yield of 87.6%.

[0144] Under nitrogen protection, 100 mL of toluene, 10 mmol of OP0V8-POSS and 96 mmol of BCB-SiH were added to a 250 mL dry three-necked flask and stirred for 30 min. Then, 5 drops of Karstedt catalyst were added dropwise. After reacting at 100 °C for 30 hours, the mixture was concentrated under reduced pressure and column chromatography was performed to obtain 17.4 g of white powder, namely OP0B8-POSS, with a yield of 90.0%.

[0145] Figure 3 NMR of OP0B8-POSS 1 H. 13 C. 29 Si spectrum data, its structure is characterized by:

[0146] 1 H-NMR (400MHz, Chloroform-d)), δ (ppm): 7.31 (d, J = 7.2Hz, 1H), 7.17 (s, 8H), 7.17 (d, J = 6.8Hz, 8H), 3.16 (s, 32H), 0.21 (s, 48H).

[0147] 13C-NMR (150MHz, Chloroform-d), δ (ppm): 147.44, 145.58, 135.58, 132.42, 127.85, 122.16, 29.98, 29.80, 7.35, 4.57, -3.32

[0148] 29 Si-NMR (119MHz, Chloroform-d), δ (ppm): -0.76, -66.39

[0149] Comparative Example 2: Closed-cage tetrabenzocyclobutenyl tetramethylbenzene polysilsesquioxane (OP0B4T4-POSS)

[0150]

[0151] The preparation of OP0V8-POSS is the same as that of Comparative Example 1.

[0152] Under nitrogen protection, 100 mL toluene, 10 mmol OP0V8-POSS, and 40 mmol BCB-SiH were added to a 250 mL dry three-necked flask, stirred for 30 min, and then 5 drops of Karstedt catalyst were added, and the mixture was reacted at 100° C. for 30 hours. Subsequently, 60 mmol T-SiH was added, and the mixture was reacted at 100° C. for another 30 hours, concentrated under reduced pressure, and 16.0 g of white powder was obtained by column chromatography, namely OP0B4T4-POSS, with a yield of 85.3%.

[0153] Figure 4 NMR of OP0B4T4-POSS 1 H. 13 C. 29 Si spectrum data, its structure is characterized by:

[0154] 1 H-NMR (400MHz, Chloroform-d)), δ (ppm): 7.50-6.96 (28H), 3.16 (s, 32H), 2.32 (12H), 0.7 (16H), 0.5 (16H), 0.22 (48H).

[0155] 13 C-NMR (150MHz, Chloroform-d), δ (ppm): 146.97, 145.60, 138.65, 133.72, 131.92, 128.69, 127.44, 122.02, 29.98, 29.80, 7.35, 4.60, -3.29, -3.42

[0156] 29Si-NMR (119MHz, Chloroform-d), δ (ppm): -0.70, -1.37, -66.35

[0157] Example 5: Thermosetting resin c-OP1B3 based on OP1B3-POSS

[0158] The open-cage OP1B3-POSS obtained in Example 3 was placed in a tetrafluoroethylene mold, and placed in a vacuum oven at a pressure of -0.08 MPa and a temperature of 90°C for 2 hours to melt it and eliminate bubbles, thereby obtaining a homogeneous, viscous POSS melt; subsequently, it was cured in three stages. In the first stage, the temperature was slowly increased to 190°C at 10°C / min and maintained for 2 hours, in the second stage, the temperature was slowly increased to 210°C and maintained for 2 hours, and in the third stage, the temperature was slowly increased to 230°C and maintained for 2 hours, thereby obtaining a thermosetting resin formed by thermal crosslinking of OP1B3-POSS, which was named c-OP1B3.

[0159] Example 6: Thermosetting resin c-OP2B4 based on double open cage OP2B4-POSS

[0160] The open-cage OP2B4-POSS obtained in Example 4 was placed in a glass mold and placed in a vacuum oven at a pressure of -0.08 MPa and a temperature of 90°C for 2 hours to melt and eliminate bubbles, thereby obtaining a homogeneous, viscous POSS melt; subsequently, it was cured in three stages. In the first stage, the temperature was slowly raised to 190°C and maintained for 2 hours, in the second stage, the temperature was slowly raised to 210°C and maintained for 2 hours, and in the third stage, the temperature was slowly raised to 230°C and maintained for 2 hours, thus obtaining a thermosetting resin formed by thermal crosslinking of OP2B4-POSS, named c-OP2B4.

[0161] Comparative Example 3: Thermosetting resin c-OP0B8 based on closed cage OP0B8-POSS

[0162] The closed-cage OP0B8-POSS obtained in Comparative Example 1 was placed in a glass mold, placed in a vacuum oven at a pressure of -0.08 MPa and a temperature of 120°C for 2 hours to melt it and eliminate bubbles, and a homogeneous, viscous POSS melt was obtained; then, it was cured in three stages. In the first stage, the temperature was slowly raised to 190°C and kept for 2 hours, in the second stage, the temperature was slowly raised to 210°C and kept for 2 hours, and in the third stage, the temperature was slowly raised to 230°C and kept for 2 hours, and a thermosetting resin formed by thermal crosslinking of OP0B8-POSS was obtained, named c-OP0B8.

[0163] Comparative Example 4: Thermosetting resin c-OP0B4T4 based on closed cage OP0B4T4-POSS

[0164] The closed-cage OP0B4T4-POSS synthesized in Comparative Example 2 was placed in a tetrafluoroethylene mold, placed in a vacuum oven at a pressure of -0.08MPa and 120°C for 2h to melt and eliminate bubbles, and a homogeneous, viscous POSS melt was obtained; then, it was cured in three stages. In the first stage, the temperature was slowly raised to 190°C and kept for 2h, in the second stage, the temperature was slowly raised to 210°C and kept for 2h, and in the third stage, the temperature was slowly raised to 230°C and kept for 2h, and a thermosetting resin formed by thermal crosslinking of OP0B4T4-POSS was obtained, which was named c-OP0B4T4.

[0165] Comparative Example 5: Bismaleimide resin c-BMI

[0166] Take 4g of commercial diphenylmethane bismaleimide and 3g of diallyl bisphenol A, and prepolymerize them at 120°C for 2 hours to form a uniform and transparent prepolymer; then, pour the prepolymer into a tetrafluoroethylene mold, place it in a vacuum oven to degas and remove bubbles, and heat it to 150°C, 180°C and 220°C for curing for 2 hours respectively. The obtained thermosetting resin is named c-BMI.

[0167] Comparative Example 6: Cyanate resin c-BADCy

[0168] Take 10g of commercial bisphenol A cyanate resin and prepolymerize it at 120℃ for 1 hour to form a uniform prepolymer. Then, pour the prepolymer into a glass mold and place it in a vacuum oven to degas and remove bubbles. The temperature is raised to 150℃, 180℃, and 220℃ for curing for 2 hours respectively, and then cured at 240℃ for 4 hours. The obtained thermosetting resin is named c-BADCy.

[0169] Test Example 1

[0170] The dielectric constant and dielectric loss of the cured materials obtained in Examples 5 to 6 and Comparative Examples 3 to 6 were tested at 25°C and 1 Hz to 1 MHz. The instrument used was a Concept 80 broadband dielectric spectrometer. The measurement results are shown in Tables 1 and Figures 5-6 As shown, Table 1 shows the dielectric properties of open-cage benzocyclobutene-based POSS resin and comparative resin at 1 MHz; Figure 5 The broadband dielectric constant data of open-cage benzocyclobutene-based POSS resin and comparative resin; Figure 6 The broadband dielectric loss data of open-cage benzocyclobutene-based POSS resin and comparative resin are shown in Figure 2.

[0171] Table 1 Dielectric properties of open cage benzocyclobutene-based POSS resin and comparative resin at 1 MHz

[0172] Dielectric constant (1MHz) Dielectric loss (1MHz) <![CDATA[Example 5, c-OP1B3]]> 2.10 0.0020 <![CDATA[Example 6, c-OP2B4]]> 1.96 0.0018 <![CDATA[Comparative Example 3, c-OP0B8]]> 2.16 0.0023 <![CDATA[Comparative Example 4, c-OP0B4T4]]> 2.17 0.0027 Comparative Example 5, c-BMI 3.31 0.013 Comparative Example 6, c-BADCy 3.03 0.007

[0173] From the above test results, it can be seen that the thermosetting resin based on the open-cage benzocyclobutene-based POSS has a lower dielectric constant than the thermosetting resin cured by the closed-cage configuration. At the same time, due to the homogeneous hybridization at the molecular level, this type of resin will not phase separate, avoiding the interface polarization of the organic-inorganic hybrid material, and its dielectric loss is maintained at 2×10 -3 At the same time, compared with traditional bismaleimide resins and cyanate resins, the dielectric constant of this type of resin at 1MHz is as low as about 2.0, and the dielectric loss value is 1 / 6 of that of bismaleimide resin.

[0174] Test Example 2

[0175] The thermal gravimetric curves of the cured materials obtained in Examples 5 to 6 and Comparative Examples 3 to 6 were tested. Figure 7 As shown in the figure, due to the presence of high surface energy and high bond energy Si-O, the open cage c-OP1B3 and c-OP2B4 resins have better thermal stability than commercial resins (c-BMI, c-BADCy). Although its thermal stability is reduced compared with the higher cross-linked closed cage c-OP0B8, it has a high thermal stability comparable to the closed cage resin c-OP0B4T4 resin with a similar cross-linking degree, and its 5% thermal weight loss temperature is still as high as 450°C or above.

[0176] Test Example 3

[0177] The Young's modulus of the cured materials obtained in Examples 5 to 6 and Comparative Examples 3 to 6 at 25° C. was tested using a nanoindentation test system. The measurement results are shown in FIG. Figure 8 As shown, the flexible open cage structure and low functionality (3 or 4) give the cured product of the open cage POSS resin a lower Young's modulus, indicating that it has better flexibility. Therefore, it can not only be prepared into a solid bulk material by casting, but also be prepared into a flexible thin film material (film thickness of about 60 μm) by spin coating or drop coating. Fig. 9 As shown in the figure, the closed cage c-OP0B8 can only be prepared into bulk samples and is difficult to be prepared into complete thin film samples; while the open cage c-OP1B3 and c-OP2B4 can be prepared not only into solid bulk materials but also into flexible thin film materials.

[0178] The organic-inorganic thermosetting resin material prepared by thermal crosslinking of open-cage polysilsesquioxane (POSS) not only has the characteristics of ultra-low dielectric constant (1.96) and low dielectric loss value (~0.002); at the same time, its 5% thermal weight loss temperature reaches above 450°C; the above properties are far superior to the currently commercially available low dielectric thermosetting resin materials (such as bismaleimide resin and cyanate resin, etc.).

[0179] Although the above-mentioned embodiments have made a detailed description of the present invention, they are only some embodiments of the present invention, rather than all embodiments. People can also obtain other embodiments based on the embodiments of the present invention without creative work, and these embodiments all fall within the scope of protection of the present invention.

Claims

1. An open-cage benzocyclobutenyl polysilsesquioxane, characterized in that: The structural formula is shown in Formula 1 or Formula 2: In the formula, R1 is selected from the following structures: phenyl, cyclohexyl, n-pentyl, trifluoro-n-pentyl or methyl; R2 is selected from the following structures: R3, R4, R5 and R6 are independently selected from the following structures: H, alkyl, cycloalkyl, cycloalkyloxy, alkylthio, alkylamino, alkenylamino, aryl, heteroaryl, substituted alkyl, substituted cycloalkyl, substituted cycloalkyloxy, substituted alkylthio, substituted alkylamino, substituted alkenylamino, substituted aryl or substituted heteroaryl.

2. The open-cage benzocyclobutenyl polysilsesquioxane according to claim 1, characterized in that: In R3, R4, R5 and R6, the alkyl group is a C1-C6 alkyl group, the cycloalkyl group is a C3-C6 cycloalkyl group, the cycloalkyloxy group is a 3-7 membered cycloalkyloxy group, the alkylthio group is a C1-C6 alkylthio group, the alkylamino group is a C1-C6 alkylamino group, the alkenylamino group is a C2-C6 alkenylamino group, the aryl group is a C6-C 12 The aryl group includes a benzo C3-C6 cycloalkyl group, the heteroaryl group is a 5-12 membered heteroaryl group, the 5-12 membered heteroaryl group contains 1-3 N, O or S heteroatoms, and the heteroaryl group includes a benzo 5-6 membered heterocyclic group.

3. The open-cage benzocyclobutenyl polysilsesquioxane according to claim 1 or 2, characterized in that: The structural formula of the open-cage benzocyclobutenyl polysilsesquioxane is shown in Formula 3 or Formula 4:

4. The method for preparing the open-cage benzocyclobutenyl polysilsesquioxane according to any one of claims 1 to 3, characterized in that: The following steps are involved: Mixing a trialkoxysilane coupling agent, an alkali metal hydroxide, water and a first organic solvent for reflux reaction to obtain an open-cage silanol alkali metal salt polysilsesquioxane; The open-cage silanol alkali metal salt polysilsesquioxane, vinyl chlorosilane, a first catalyst and a second organic solvent are mixed to carry out an etherification reaction to obtain a vinyl open-cage polysilsesquioxane; The vinyl open-cage polysilsesquioxane, the benzocyclobutenyl silane compound, the second catalyst and the third organic solvent are mixed to carry out a hydrosilylation reaction to obtain an open-cage benzocyclobutenyl polysilsesquioxane; The structural formulas of the trialkoxysilane coupling agent, vinyl chlorosilane, and benzocyclobutenyl silane compound are shown in Formula 5, Formula 6, and Formula 7, respectively:

5. The preparation method according to claim 4, characterized in that: The alkoxy group in the trialkoxysilane coupling agent is a methoxy group or an ethoxy group.

6. The preparation method according to claim 4 or 5, characterized in that: The molar ratio of the alkali metal hydroxide to the trialkoxysilane coupling agent is 1:1.5 to 1:

3.

7. The preparation method according to claim 4, characterized in that: The molar ratio of the alkali metal element to vinyl chlorosilane in the open-cage silanol alkali metal salt polysilsesquioxane is 1:2 to 1:

4.

8. The preparation method according to claim 4, characterized in that: The molar ratio of the vinyl group to the benzocyclobutene silane compound in the vinyl open cage polysilsesquioxane is 1:1 to 1:1.

5.

9. Use of the open-cage benzocyclobutenyl polysilsesquioxane according to any one of claims 1 to 3 or the open-cage benzocyclobutenyl polysilsesquioxane obtained by the preparation method according to any one of claims 4 to 8 in the field of electrical communications.

10. A solidifying material, characterized in that: The curing material is obtained by cross-linking and curing the open-cage benzocyclobutenyl polysilsesquioxane described in any one of claims 1 to 3 or the open-cage benzocyclobutenyl polysilsesquioxane obtained by the preparation method described in any one of claims 4 to 8.

Citation Information

Patent Citations

  • High-heat-resistance resin and preparation method thereof

    CN117327275A

  • Open-structure polyhedral oligomeric silsesquioxane and composition comprising same

    WO2014193177A2

Cited By

  • Preparation method and application of functionalized MQ silicon resin

    CN122541719A